Selection of the Best Process Stream to Remove Ca2+ Ion Using Electrodialysis from Sugar Solution. (14th December 2014) - Tadimeti, Jogi Ganesh Dattatreya; Jain, Shilpi; Chattopadhyay, Sujay; Bhattacharya, Prashant Kumar
Abstract : Electrodialytic removal of calcium chloride (CaCl2, 25–50 mol·m −3 ) from 5% sugar solution was executed in batch recirculation mode. Calcium ion removal rate was monitored with (i) applied potential, (ii) feed flow rate, (iii) solution viscosity and conductivity, and (iv) catholyte streams (NaOH or sodium salt of ethylene diamine tetraacetic acid-acetic acid, Na2 EDTA-AA). Unsteady state model for ion concentration change was written for the ED cell used. Linearized Nernst-Planck equation instead of Ohm's law was applied to closely obtain the current density and concentration change theoretically. The model developed could closely predict the experimental observation. Mass transfer coefficients and specific energy densities were estimated for each combination of catholyte stream used. NaOH showed better performance for a short duration over Na2 EDTA-acetic acid combination.